Epidemiological Investigation Report of Food Poisoning in Banjarsari, Kanigoro District, Blitar Regency, 2025 - Widyawati Ratnasariani; Rismawati Rismawati; Siti Shofiya Novita Sari; Endro Pramono (Rifa'Institute, 2026)
Introduction: Food poisoning is still one of the causes of extraordinary events (KLB) that often occur in community activities, especially at events with large amounts of food processing. Epidemiological investigations are necessary to identify patterns of occurrence, risk factors, and possible sources of exposure. Objective: This study aims to describe the pattern of occurrences, analyze risk factors, and identify possible sources of food poisoning in KLB in Banjarsari Village, Kanigoro District in 2025. Method: A descriptive observational investigation used case interviews, epidemic curve analysis, attack rate and attack rate ratio calculations, laboratory testing of food remnants, and observations. Result and Discussion: The epidemic curve indicated a common-source outbreak, with incubation periods ranging from 4 to 29 hours. Several foods showed high attack rates, but attack rate ratios were close to one, indicating no single dominant food source. Laboratory tests of three food samples were negative for pathogenic bacteria, although sample limitations and the absence of clinical specimens reduced interpretation. Environmental assessment identified unsafe food processing and storage practices. Conclusion: The incidence of food poisoning in Banjarsari Village, Kanigoro District in 2025 is a common source outbreak that is most likely caused by a combination of food processing factors that do not meet sanitary hygiene standards, inappropriate food storage, and risky environmental conditions, even though laboratory test results show negative results